Blood years - Arnold, Elana K. (New York, NY Balzer + Bray, an imprint of HarperCollins Publishers, 2023)
"Frederieke Teitler and her sister, Astra, live in a home, in a city, in a world divided. Their father left when Rieke was only six, leaving their mother a wreck and their grandfather as their only stable family. He's done his best to provide for them and shield them from antisemitism, but now being a Jew has become increasingly dangerous, even in their beloved home of Czernowitz, long considered a safe haven for Jewish people. And when Astra falls in love and starts pulling away from her, Rieke wonders if there's anything in her life she can count on -- and if she has the power to hold on to it. Then war breaks out in Europe. First the Russians, then the Germans, invade Czernowitz. Almost overnight, Rieke and Astra's world changes, and every day becomes a struggle: to keep their grandfather's business, to keep their home, to keep their lives. Rieke has long known that she exists in a world defined by those who have power and those who do not, and as those powers close in around her, she wonders if holding on to her life might mean letting go of everything else -- if that's a choice she will even have the chance to make. Based on her grandmother's experiences in Holocaust-era Romania, National Book Award finalist and Printz honoree Elana K. Arnold weaves a heartbreaking tale of love and loss in the darkest days of the twentieth century -- and one young woman's will to survive them." --
Foreword -- A brief history of Czernowitz -- Part I: Astra and her lover -- Pigeons and promises -- The way things are -- Cafe Europa -- How to fix things -- Welcome to the blood years -- Broken, and breaking -- Part II: The Russian year -- The goose and the bear -- When flying monkeys attack -- When time stops -- The Moiseyev dancers -- Honeymoons, waxing and waning -- Masks on -- The narrowing gyre -- What happens to Ruth -- Part III: A very lucky girl -- The Nazis -- Never pray for a new king -- Into the ghetto -- Unexpected heroes -- In Mr. Weissinger's apartment -- How lucky -- Part IV: What it costs -- Right now -- Payment in advance -- Treatment -- The wheelbarrow -- The locket -- Part V: In the name of love.
Includes bibliographical references (pages 383-387).
Grades: 9 and up
Ages: 14 and up
Sydney Taylor Young Adult Award, 2024.
National Jewish Book Award, Young Adult Literature, 2023.
113752
Keywords: 1914-1945; Holocaust, Jewish -- Romania -- Juvenile fiction. -- (1939-1945); Grandfathers -- Juvenile fiction; Jews -- Juvenile fiction; Sisters -- Juvenile fiction; Jewish families -- Juvenile fiction; World War -- Romania -- Juvenile fiction. -- 1939-1945; Coming of age -- Fiction; Young Adult Fiction -- Historical -- Holocaust; Young Adult Fiction -- Family -- Multigenerational; Grandfathers; Jews -- Juvenile fiction; Germany; Young adult fiction; History; Juvenile works; Historical fiction; Domestic fiction; War fiction; Religious fiction; Fiction; Children's / Teenage fiction: Family & home stories; Children's / Teenage fiction: Historical fiction; Children's / Teenage personal & social issues: Family issues; Interest age: from c 12 years; Children's / Teenage fiction: General fiction; Children's / Teenage fiction: Religious fiction; Europe; Germany: National Socialist period (19331945); Relating to Jewish people & groups; Fiction 11+; Children's and Teenage: Family Stories